How to dissolve The moral problem - Suikkanen Jussi (Belgrade Philosophical Annual)
According to Michael Smith, there is so much metaethical disagreement because it is difficult to explain both the objectivity and the practicality of moral judgments in the framework provided by the Humean picture of human Psychology. Smith himself hoped to solve this problem by analysing the content of our moral judgments in terms of what our fully rational versions would want us to do. This paper first explains why this solution to the moral problem remains problematic and why we therefore are no closer to solving the problem. It then outlines how the moral problem could perhaps be dissolved instead. The second half of the paper thus first reconstructs the moral problem in the framework of dispositionalism about belief. It then suggests that, if we think of moral beliefs in dispositionalist terms and take 'believe' to be a vague predicate, we can come to see why many of the most fundamental metaethical questions cannot be answered. The last section of the paper then extends this method of dissolving metaethical questions to other popular views about belief.